2017
DOI: 10.1016/j.biortech.2016.10.055
|View full text |Cite
|
Sign up to set email alerts
|

Pilot scale biodiesel production from microbial oil of Rhodosporidium toruloides DEBB 5533 using sugarcane juice: Performance in diesel engine and preliminary economic study

Abstract: A successful pilot-scale process for biodiesel production from microbial oil (Biooil) produced by Rhodosporidium toruloides DEBB 5533 is presented. Using fed-batch strategy (1000L working volume), a lipid productivity of 0.44g/L.h was obtained using a low-cost medium composed by sugarcane juice and urea. The microbial oil was used for biodiesel production and its performance was evaluated in diesel engine tests, showing very good performance, especially for the blend B20 SCO, when operating at 2500rpm with low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
98
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(104 citation statements)
references
References 22 publications
2
98
0
4
Order By: Relevance
“…The composition of these oils indicates that they are suitable as raw material for the production of biodiesel (Soccol et al, 2017). have found similar effects on root size and number of lateral roots for bean seedlings (Gupta et al, 2016).…”
Section: Saitoana T Ducitum T Miniiliforme T Lignícola Tmentioning
confidence: 86%
“…The composition of these oils indicates that they are suitable as raw material for the production of biodiesel (Soccol et al, 2017). have found similar effects on root size and number of lateral roots for bean seedlings (Gupta et al, 2016).…”
Section: Saitoana T Ducitum T Miniiliforme T Lignícola Tmentioning
confidence: 86%
“…It has been indicated that the overall biodiesel production cost was economically competitive (0·76 US$ per l) to that of vegetable biodiesel (respective cost 0·81 US$ per l) and the yield of biodiesel was 6·3‐fold higher (4172 l per ha of cultivated sugarcane) than that obtained from yield of soybean biodiesel (661 l per ha of cultivated soybean; Soccol et al . ).…”
Section: Oleaginous Micro‐organismsmentioning
confidence: 97%
“…In contrast to the above-mentioned consideration, another more recently presented scenario of second-generation biodiesel production witnesses cost-effective pilot-scale biodiesel production of Rhodosporidium toruloides DEBB 5533 using a low-cost medium composed of sugarcane juice and urea (1000 l working volume). It has been indicated that the overall biodiesel production cost was economically competitive (0Á76 US$ per l) to that of vegetable biodiesel (respective cost 0Á81 US$ per l) and the yield of biodiesel was 6Á3-fold higher (4172 l per ha of cultivated sugarcane) than that obtained from yield of soybean biodiesel (661 l per ha of cultivated soybean; Soccol et al 2017).…”
Section: Oleaginous Micro-organismsmentioning
confidence: 99%
“…An alternative cost effective approach to the microbial oil for biodiesel production is to co-produce medically and dietetically important polyunsaturated fatty acids (PUFA) such as γ-linolenic, dihomo-γlinolenic, arachidonic, and eicosapentaenoic acid [61][62][63][64]. Contrary to these assumptions, the recent scenario of biodiesel production witness cost effective pilot-scale biodiesel production of Rhodosporidium toruloides DEBB 5533 using a low-cost medium composed of sugarcane juice and urea [65]. They showed that the overall biodiesel production cost was economically competitive (US$ 0.76/l) to that of vegetable biodiesel (US$ 0.81/l) and the yield of biodiesel is 6.3-fold higher (4172 l/ha of cultivated sugarcane) than that obtained from yield of soybean biodiesel (661 l/ha of cultivated soybean) [65].…”
Section: Low-cost Substrates Utilized By Oleaginous Yeasts To Producementioning
confidence: 99%
“…Contrary to these assumptions, the recent scenario of biodiesel production witness cost effective pilot-scale biodiesel production of Rhodosporidium toruloides DEBB 5533 using a low-cost medium composed of sugarcane juice and urea [65]. They showed that the overall biodiesel production cost was economically competitive (US$ 0.76/l) to that of vegetable biodiesel (US$ 0.81/l) and the yield of biodiesel is 6.3-fold higher (4172 l/ha of cultivated sugarcane) than that obtained from yield of soybean biodiesel (661 l/ha of cultivated soybean) [65]. Besides this various low-cost raw materials such as sugarcane molasses (SCM) are extensively used as raw materials for oleaginous yeast due to its availability and high sugars contents [66].…”
Section: Low-cost Substrates Utilized By Oleaginous Yeasts To Producementioning
confidence: 99%